Impact of floods on undernutrition among children under five years of age in low- and middle-income countries: a systematic review - Agabiirwe, Caroline Noel; Dambach, Peter; Methula, Thabile Constance; Phalkey, Revati (Environmental health, 2022)
Weather and climate-related disasters, including floods, impact undernutrition through multiple pathways, including food security, inadequate child care practices, and water and sanitation. This review aimed to provide systematic evidence of the impact of floods on undernutrition in children under five years of age in Low and Middle-income countries (LMICs).
Gesehen am 04.01.2023